Modeling Graduate Emigration in Nigeria Using Log-linear Approach - O.S. Balogun; A.A. Akinrefon; S.S. Abdulkadir; A.M. Yami; D.F. Bright (University of Sofia, 2014)
This research work was carried out as a result of the alarming rate at which graduates in Nigeria, which should form the bulk of our nation's workforce and ensure the growth and development of our great nation, leave our shores in search of greener pastures. The main focus of this research work is to develop models that can be used to study the trend of graduate emigration in Nigeria using log-linear modeling based on the results from of likelihood ratio (G2), Akaike Information Criteria (AIC) , Saturated model has a perfect fit for modeling graduate emigration in Nigeria. This implies all the three factors involved (discipline, year and sex) has to be included in the model in order to have an appropriate result.